Pengaruh Media Interaktif 3D terhadap Minat Belajar, Kemandirian Belajar, dan Pemahaman Konsep IPA Biologi Peserta Didik Kelas VIII di SMP Negeri 6 Bulukumba - Misrah, Misrah; Palennari, Muhiddin; Bahri, Arsad (Universitas Negeri Makassar, 2024)
This study is a quasi-experimental research that aims to examine the influence of 3D interactive media on learning interest, independent learning, and conceptual understanding of grade VIII at SMPN 6 Bulukumba. The research population were grade VIII students at SMPN 6 Bulukumba for the 2022/2023 academic year with a total of 50 students. Samples were taken by employing purposive sampling technique. Data collecting employed questionnaire and test techniques. Data on learning interest and independent learning were collected by using a questionnaire and understanding the material was collected by using multiple choice test. Data were analyzed by using descriptive analysis and inferential analysis. The results of the hypothesis test using the ANACOVA test (Analysis of Covariance) show that the significance value of learning interest is sig < α = 0.05 or 0.001 < α = 0.05, which means H1 is accepted. Likewise, the learning independence sig < α = 0.05 or 0.001 < α = 0.05, which means H1 is accepted. As well as material understanding sig < α = 0.05 or 0.001 < α = 0.05, which means H1 is accepted. Based on these test criteria, it can be concluded that there is an influence of 3D interactive media on learning interest, independent learning, and conceptual understanding of grade VIII at SMPN 6 Bulukumba.